Cooling the Heat Island in Compact Urban Environments: The Effectiveness of Chicago's Green Alley Program. (2015) - Coseo, Paul; Larsen, Larissa
Abstract: To build 21st century sustainable cities, officials are installing alternative infrastructure technologies to reduce atmospheric environmental problems such as the urban heat island (UHI). The purpose of this study is to further our understanding of how ground-level UHI mitigation strategies in compact urban areas impact air temperatures. The term 'cool pavement' refers to both reflective and porous pavements. While cool pavements are identified as UHI mitigation strategies, we evaluated their in-situ effectiveness on air and surface temperatures. Using a case-control research design, we measured the impact of these pavements on air temperature relative to conventional asphalt in alleys. In locations where high vertical walls constrained the release of solar radiation, reflective pavements increased air temperatures. In two neighborhoods, reflective concrete increased daytime 3-meter air temperatures by 0.9° C and 0.5° C respectively and had no influence on nighttime temperatures. Unlike reflective pavement, porous pavements permit percolation and may contribute to cooling through evaporation. However, our research illustrated that porous asphalt and porous concrete increased maximum daytime air temperatures by 0.8° C and 0.5° C and did not lower nighttime air temperatures. While porous concrete pavers had significantly warmer midday air temperatures, it was the only cool pavement strategy to yield lower early evening air temperatures relative to conventional asphalt. Even immediately after rain events, the air temperatures above the porous pavements were not significantly cooler. This research demonstrates our need to evaluate real world installations of cool pavement to determine their actual impact on decreasing summertime temperatures.